Evaluasi Usability Website library.umn.ac.id Universitas Multimedia Nusantara - Melanesia N.W. Rumbiak; Johan Setiawan (ULTIMA InfoSys, 2017)
Abstract – The library.umn.ac.id is the library website which is owned by the Universitas Multimedia Nusantara. The website has never been examined with usability especially its user interfaces. In conducting the evaluation, the methods of usability tests are applied that is users’ observations of the website user interface design continued by collecting and analyzing data. In addition, data is collecting by creating a questionnaire which is based on System Usability Scale (SUS) to measure users’ satisfaction when using the system. The data is analyzed by applying usability test that refers to the theory of Jacob Nielsen (2003) which is composed of five components that are learnability, efficiency, memorability, errors, and satisfaction. The results of this research, some new user interfaces are recommended for enhancing the library website that has been fully the old version. As a result, the user interfaces prototype is easy to use and easy to understand based on the students’ responses compared to the old version. Keywords-Usability Evaluation, User Interface, Usability Testing, System Usability Scale